IN VITRO EVALUATION OF CYTOTOXIC AND GENOTOXIC EFFECTS OF PLANT EXTRACTS FROM NOTHAPODYTES FOETIDA (WIGHT) SLEUMER (FAMILY: ICACINACEAE) - D Datkhile, Kailas; P Durgawale, Pratik; N Patil, Madhavi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to investigate cytotoxic and genotoxic properties of aqueous and methanolic extracts of the aerial parts of Nothapodytes foetida (Wight) Sleumer plant. Methods: The cytotoxic effects of aqueous and methanol extract of leaves and stem bark on cell viability of HeLa, MCF7, and HCT-15 cell lines was determined by 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazoliumbromide assay. We also confirmed the genotoxic effects of plant extracts through DNA fragmentation in cancer cells and expression pattern of apoptotic genes including p53 and caspase-3 analyzed by semiquantitative reverse transcription-polymerase chain reaction and western blotting techniques. Results: The present study revealed that, when plant extract was tested for cytotoxic activity, the data obtained from cell viability results of HeLa and MCF7 cells revealed that methanol extract of leaves and stem bark exhibited a range of significant cytotoxic activities in a dose-dependent manner varying from 2.5 to 25 Î¼g/mL, whereas an aqueous extract of leaves and stem bark showed decreased cell viability with an increase in the concentration of both the extracts from 5 to 50 Î¼g/mL. Conclusion: These results indicated that the crude extract aerial parts of N. foetida plant contain promising substances having a potential as cytotoxic agent.